Sistemas construtivos pré fabricados: uma abordagem Enxuta - Cunha, José Camillo Barbosa da; Palha, Rachel Perez; Régis, Paulo de Araújo (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
With the advent of the 4th industrial revolution and disruption with traditional methods of construction, the pre-fabrication of constructive systems has never been so prominent. The competitiveness of the sector and the complexity of the projects have increased substantially, so that the survival of companies in this sector is associated with their ability to optimize resources and decrease the waste of their production. Thus, the application of Lean Manufacturing concepts, which focus on waste reduction, presents itself as an alternative not only viable, to provide mapping and waste reduction tools, but also desirable, by philosophically approaching the entire system in the which the company is inserted, positively impacting the company culture. The objective of this work is to indicate, within a flow chart of activities of a real company, points where Lean concepts and tools would add value to the process. To this end, the production stages were raised, detailing the macro-processes of armature, set-up of forms, concreting and preparation for shipment, in order to identify points where some of the tools of Lean's philosophy could be applied.